Pelatihan Baca Syair Siswa Kelas IX SMP Negeri 6 Siak Hulu Kabupaten Kampar - Shomary, Sudirman; Yuliawan, Tri; Roziah, Roziah; Sudirman, Nurul Aini (UIR Press, 2025)
Learning to recite or reply to rhymes is very important for junior high school students. In addition to practicing literary skills, reciting rhymes can also train students' mental abilities to perform in front of many people. In addition, rhyming can also build students' character and personality because rhymes contain many messages and moral values. The difficulty of reciting rhymes occurs a lot in the high school environment. Many teachers complain when their students are reluctant to perform pantun recitation. This happens because students have not gained the right learning experience in rhyming. This kind of learning needs to be addressed, so it is necessary to hold a rhyme reading training for high school students which can be done by practicing proper pronunciation, tone, stress, intonation, appreciation, and expression. The problem of this activity is how to improve the knowledge and skills of rhyming students of Class IX SMP Negeri 6 Siak Hulu, Kampar Regency? The purpose of this community service activity is to provide knowledge and practice of reading or replying to rhymes in accordance with good and correct techniques. The method of community service uses lecture and experimental methods. The speaker explains the theory of rhymes and how to read or reply to good rhymes. The rhymes used are Syair Nasehat author Tenas Effendy. Based on the success criteria, SMP Negeri 6 Siak Hulu students in Kampar Regency have been able to recite rhymes, after the training was completed. This was shown by the students' enthusiasm when the community service team asked them to recite a poem in front of the class. They have been able to pronounce, intonate, cut words, and express them appropriately. Thus, this training activity can be said to be successful. After the training was conducted, participants were given a questionnaire on partner satisfaction with PKM activities for Class IX SMP Negeri 6 Siak Hulu, Kampar Regency. The questionnaire was used to determine the participants' knowledge after the training was given.